Correlation between ultrasound velocity and densitometry in fresh and demineralized cortical bone (Clinics, 2016)
OBJECTIVE: To compare ultrasound propagation velocity with densitometry in the diaphyseal compact cortical bone of whole sheep metatarsals. METHODS: The transverse ultrasound velocity and bone mineral density of 5-cm-long diaphyseal bone segments were first measured. The bone segments were then divided into four groups of 15 segments each and demineralized in an aqueous 0.5 N hydrochloric acid solution for 6, 12, 24 or 36 hours. All measurements were repeated after demineralization for each time duration and the values measured before and after demineralization were compared. RESULTS: Ultrasound velocity and bone mineral density decreased with demineralization time, and most differences in the pre- and post-demineralization values within each group and between groups were significant: A moderate correlation coefficient (r=0.75956) together with a moderate agreement was determined between both post-demineralization parameters, detected by the Bland-Altman method. CONCLUSION: We conclude that both ultrasound velocity and bone mineral density decrease as a result of demineralization, thus indicating that bone mineral content is of great importance for maintaining the acoustic parameters of cortical bone, as observed for cancellous bone. Ultrasound velocity can be used to evaluate both compact cortical bone quality and bone mineral density.